KEEFEKTIFAN MANAJEMEN BERBASIS SEKOLAH DALAM UPAYA PENINGKATAN PRESTASI BELAJAR SISWA DI SD UNGGULAN ‘AISYIYAH BANTUL - Triningsih (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
The purpose of this study is to describe the effectiveness of School Based Manajement (SBM) in effort to increase student achievement at Unggulan 'Aisyiyah Bantul, Yoggyakarta and the type of study is qualitative. The data collection technique used observation, documenttation and indeep interview. The respondents of the interview were the shcool principal, vice-principals, teacher, and representatives of parents. Data analysis technique was conducted by reducing data, presenting data, and drawing conclusion. The validity of the data was obtained by doing triangulation, discussion, and checking members. The result of this study showes that the implementation of SBM at SD Unggulan 'Aisyiyah Bantul is effective through the implementation of six management components, that is self-evaluation, formulating vision/mission/goal, planning, application, evaluation and reporting. It is also appropriate to the essence of SBM, that is otonomy, flexibility, participation, transparancy, and accountability.